Scaling up resilient agricultural practices, technologies and services in the vulnerable areas of India - Khatri-Chhetri, Arun; Pande, Kunal; Pant, Anjali; Sahin, Shehnab (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
The brochure contains details of a project intervention funded by USAID, to scale out the Climate-Smart Villages in three Indian states of Uttar Pradesh, Bihar and Madhya Pradesh.